Continuous Differential Microemulsion Polymerization to Prepare Nanosized Polymer Latices in Microreactors - Min Qiu; Liang Xiang; Minjing Shang; Yuanhai Su (Advances in Polymer Technology)
Microreactors are a promising platform for continuous synthesis of polymer latices when combined with emulsion polymerization. However, this application has long been haunted by fouling and clogging problems. In this work, we proposed the strategy of conducting differential microemulsion polymerization in microreactors within a biphasic slug flow and achieved rapid and stable preparation of nanosized PMMA latices (polymeric content as high as 15.7% with average particle size smaller than 20 nm). We started by exploring the temperature thresholds with thermal and redox initiation, the effect of initiator concentration, and the kinetic characteristics of microemulsion polymerization at different temperatures. Then, as for the differential microemulsion polymerization, extensive investigation was made into the effects of the volumetric flow ratio, the prepolymerization time, the initiator concentration, and the solid content of the initial microemulsion. Finally, we compared the differential microemulsion polymerization with the soap-free emulsion polymerization in the slug flow. The striking advantages in the polymerization rate, the average particle diameter, and the size distribution reflected higher density of particle nuclei, larger specific surface area of particles, and the pivotal effect of the persistent particle nucleation in the microemulsion polymerization.